Fostering computational thinking among underrepresented students in STEM : strategies for supporting racially equitable computing /: strategies for supporting racially equitable computing. (2021) - Leonard, Jacqueline; Thomas, Jakita, 1977-; Ellington, Roni M; Mitchell, Monica B; Fashola, Olatokunbo S
No abstract available